Simulation of Piko Hydro Power Generator Using Thread Turbine With 10 Watt Power - Afrizal Abdi Musyafiq; Novita Asma Ilahi; Riyani Prima Dewi; Usman Barokah (Jurnal Jaringan Telekomunikasi, 2022)
Renewable energy is one of the efforts to utilize electricity from renewable energy sources. Hydroelectric power is one of the plants that utilizes water as the main energy. Although the amount of energy is abundant, but in Indonesia the use of water as a power plant is still below 7%. This is due to the lack of human resources to manage water energy. Therefore, in this study, a simulation of a pico-hydro power plant using a screw turbine was designed which is expected to provide benefits. This tool is equipped with digital monitoring using Arduino Uno. Power monitoring on this tool uses the INA219 power sensor which is displayed on the LCD display. This tool uses a 12-24V DC generator. The turbine used is a screw turbine type. This pico-hydro power plant simulation is capable of turning on a load equivalent to 1 lamp of 10 watts/12 VAC with an inverter. The measurement of the current and voltage of the generator shows that the average current reaches 11.75 mA and the average voltage produced is 2.11 VDC and the power generated is 24.82 mW. The resulting step-up voltage measurement to charge the battery is 13.04 VDC and the current is 12.4 mA and the battery charging power is 0.161 watts.